PENGARUH BUDAYA ORGANISASI, KOMITMEN ORGANISASI DAN GAYA KEPEMIMPINAN TERHADAP KINERJA KARYAWAN - ASIH ANDAYANI ANDAYANI; Tjiptogoro Dinarjo Soehari (Akademika, 2019)
Commitment and leadership style both simultaneously and partially on the performance of employees of the National Professional CertificationBoard in Jakarta. The methodology used in this study is the Quantitative Method, a data processing method that explains the influence and the relationship stated by sentence. Quantitative analysis is used to see the causal factors. The variables used are Employee Performance (Y) as the dependent variable while Organizational Culture (X1), Organizational Commitment (X2) and Leadership Style (X3) as independent variables.The variables used are Employee Performance (Y) as the dependent variable while Organizational Culture (X1), Organizational Commitment (X2) and Leadership Style (X3) as independent variables. This research was conducted at the National Professional Certification Board with a population of 34 people and used a saturated sample